Stress of the COVID-19 and its Consequences on Irritable Bowel Syndrome Patients in A Selected Tertiary Level Hospital in Bangladesh - Ghosh, Dilip Kumar; Sarker, Debashis Kumar; Ullah, Parash; Nath, Mukta; Chowdhury, Shamsuddin Al Masud; Bashar, Khondaker Abul; Rahut, Antora; Mahmuduzzaman, Mohammad (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: The COVID-19 pandemic represents a multiple stress. Stress can worsen the symptoms of (IBS) patients. Aims & Objective: The aim of the study was to assess the stress of COVID -19 and its impact on IBS patients during the pandemic situation among the Bangladeshi population. Methods: This cross-sectional study was conducted among the self-reported previously diagnosed IBS patients aged 18 years and above, irrespective of sex, in the Gastroenterology department of ShaheedSuhrawardy Medical College Hospital. Data was collected by a structured questionnaire which included the patient’s socio-demographic, clinical symptoms of IBS, personal habits, comorbidities, self-reported stress due to COVID-19, and its effect on the symptoms of IBS. Results: The study respondents consisted of 210 IBS patients, among them 71.90% were male and 28.10% were female. The majority of the study population (43.0%) belonged to age group of 31-40 years and mean age 35.12 ± 11.55 years. Most of the respondents (91.9%) reported stress due to the COVID-19 pandemic. The most commonly reported causes of stress were fear of a family member being infected with the virus (94.8%), followed by fear of self-infection (90.5%), and death due to COVID-19 infection (68.1%). Most of the stressed respondents (72.9%) reported that stress usually exaggerates IBS symptoms. Almost 25.7% of the subjects consulted a physician for stress aggravation of the symptoms, 21.0% used sedatives due to stress, and 21.0% modiﬁed IBS medications due to stress. Moreover, 36.2% of the participants reported hampered daily activities due to IBS symptoms exacerbation. Conclusion: The study revealed that most of the IBS patients had been suffering from stress during the COVID-19 pandemic situation. IBS patients should be advised to participate in mental health education programs to adjust to the current pandemic COVID-19 situation. J Shaheed Suhrawardy Med Coll 2022; 14(1): 50-56